The culture of hope and ethical challenges in clinical trials: A qualitative study of oncologists and haematologists' views. (March 2020) - Godskesen, Tove E; Petri, Suzanne; Eriksson, Stefan; Halkoaho, Arja; Mangset, Margrete; Nielsen, Zandra E
We do not know how much clinical physicians carrying out clinical trials in oncology and haematology struggle with ethical concerns. To our knowledge, no empirical research exists on these questions in a Nordic context. Therefore, this study aims to learn what kinds of ethical challenges physicians in Sweden, Denmark and Finland (n = 29) face when caring for patients in clinical trials; and what strategies, if any, they have developed to deal with them. The main findings were that clinical cancer trials pose ethical challenges related to autonomy issues, unreasonable hope for benefits and the therapeutic misconception. Nevertheless, some physicians expressed that struggling with such challenges was not of great concern. This conveys a culture of hope where health care professionals and patients uphold hope and mutually support belief in clinical trials. This culture being implicit, physicians need opportunities to deliberately reflect over the characteristics that should constitute this culture.